Estimation of Radiation Dosimetry for some Common SPECT-CT Exams - Mhiri, Aida; Slim, Ihsen; Ghezaiel, Mohamed; Slimène, Mohamed Faouzi Ben (International Journal of Biotechnology for Wellness Industries, 2013)
Single photon emission computed tomography associated to X ray computed tomography (SPECT-CT) is a nuclear medicine tomographic imaging technique which improves diagnostic accuracy for particular clinical indications due to the possible attenuation and/or scatter correction of the SPECT functional images and the availability of helpful anatomic information. However, the introduction of CT in the nuclear diagnostic process results in a significant increase of the patient dose. Ideally is to establish sufficient image quality for a specific diagnostic task with the lowest effective dose to the patient in order to reduce stochastic effects. Indication of SPECT-CT should be made to adhere to the “As Low as Reasonably Achievable (ALARA)” principle and ensure that the patient is not subjected to unnecessarily high levels of radiation. In this study, we evaluate effective doses received during some standard nuclear medicine exams from 100 patients who underwent SPECT-CT in our department and analyze parameters involved in variation of these doses according to the literature data.